Preserving Indigenous Culture or Spreading Multiculturalism Across Europe? – Challenges of EU Migration Policy - Tamar Todria (European Scientific Journal, ESJ, 2017)
One of the main consequences of the globalization process is migration flows. As the world globalizes intensively and borders become open easily the issue of migration raises. Migration has become the defining issue of the 21st century. Migration or more appropriately, human mobility is vital for global prosperity. Migrants make contributions not only for their countries of destination but for the country of origin as well, but it still remains to be the controversial issue. Sometimes this process is perceived as a positive and beneficial for the countries, but it might be transformed in a problem as well. It depends on the type of this process. Thorough analyze should be done to investigate how the migrants are treated by each country and deep analyze should be done to see what is the link between the policies and aptitudes of the migrants. It’s very interesting to decipher what is the correlation between the existing migration policy of the European Union and the status quo of the migrants, more precisely how effective is the current policy. Particularly, to conclude how paper based regulations/restrictions work in practice and how effective are they. How does the European Union stipulation for the idea “Unity in Diversity”, work in practice? Borders themselves may just be lines, but crossing them changes many things. For example, you may find yourself in a totally different cultural surrounding with different religion, food, language or money. Being born one meter to the right or to the left of this artificial line determines us. It is so bizarre to think that one kilometer can change all of your life.